Language and space - Bloom, Paul (Language, speech, and communication, 1996)
* The architecture of the linguistic-spatial interface / Ray Jackendoff * How much space gets into language? / Manfred Bierwisch * Perspective taking and ellipsis in spatial description / Willem J. M. Levelt * Frames of reference and Molyneux's question: Crosslinguistic evidence / Stephen C. Levinson * The confluence of space and language in signed languages / Karen Emmorey * Fictive motion in language and "ception" / Leonard Talmy * The spatial prepositions in English, vector grammar, and the cognitive map theory / John O'Keefe * Multiple geometric representations of objects in languages and language learners / Barbara Landau * Preverbal representation and language / Jean M. Mandler * Learning how to structure space for language: A crosslinguistic perspective / Melissa Bowerman * Space to think / Philip N. Johnson-Laird * Spatial perspective in descriptions / Barbara Tversky * A computational analysis of the apprehension of spatial relations / Gordon D. Logan and Daniel D. Sadler * The language-to-object perception interface: Evidence from neuropsychology / Tim Shallice * Space and language / Mary A. Peterson, Lynn Nadel, Paul Bloom and Merrill F. Garrett